Evaluate the fixed measurement of things value by JOD– Historical Study - Abdullah Ibrahim Nazal; Ahmed Makhlouf (Journal of North African Economies, 2025)
This study aims to find the Jordanian Currency (JOD) possibility to become a fixed measurement for things value. The study methodology is collecting the directions of Jordanian foreign reserve by Central Bank of Jordan (CBJ) based to its annual reports during 1964-2022. Searchers used tables to find behavior of its changing every year as a qualitative and historical study. The result shows that JOD is not a fixed measurement for things value in long term because of international standards changings. These changing caused loss of gold covering to buy things and reduce Jordanian foreign currencies value, such as every gold ounce was equal 35 USD at time of building the Jordanian foreign reserve in 1964 but now it about 2000 USD. The changing is continues impacting accepted levels of guarantee and liquidity negatively. Searchers suggested to increase local producing to cover local needs than import and to buy gold.